Fostering Tauhid Values Through Quranic Farm-Based Learning at SMP Sekolah Quranpreneur Indonesia - Jummiana Jummiana (STAI Hubbulwathan Duri, 2023)
This study aims to explore the instillation of Tauhid (monotheism) values through Quranic farm-based learning at SMP Sekolah Quranpreneur Indonesia. Tauhid, the Islamic concept of the oneness of Allah, is essential in shaping students' spiritual and moral development. Integrating it with practical learning methods like farming provides a unique pedagogical approach that combines religious teachings with hands-on activities. The research employed a qualitative methodology to provide an in-depth understanding of the processes involved. Data were collected through interviews, observations, and documentation, offering multiple perspectives on the teaching and learning activities. Data analysis followed the steps of data reduction, data presentation, and drawing conclusions. The findings reveal that the instillation of Tauhid values is carried out through both in-class and outdoor learning activities. In the classroom, students are taught the principles of Tauhid through traditional instructional methods. Outside the classroom, students engage in gardening practices where they integrate Tauhid values with hands-on activities. During these gardening sessions, students recite and memorize Quranic verses (murojaah) while caring for the plants. This dual approach serves to reinforce the values of trust in Allah, gratitude, patience, and justice through both spiritual and practical dimensions. The integration of Tauhid values into practical learning activities like farming helps to deepen students' understanding and appreciation of these values. The combination of classroom instruction and experiential learning in the garden creates a holistic learning experience that connects religious knowledge with everyday practices. This study highlights the importance of creative teaching approaches in instilling core spiritual values in students. The study concludes that Quranic farm learning is an effective method for instilling Tauhid values in students. By combining classroom teaching with practical gardening activities, students are able to internalize the principles of Tauhid in a meaningful way. Future research could further explore the impact of such integrative learning models on student development in other educational settings.